The Antioxidant Activity Comparison of Malus sylvestris Mill and Its Processed Products - Engrid Juni Astuti; Agustin Rafikayanti; SeptianaTita Purwanto; Chenchen Puspitasari; Wenni Fista Rika; Yeni Yesica (Universitas Dr Soetomo, 2021)
Chemical compounds that can donor one or more electrons to free radicals to inhibit free radical reactions are called antioxidants. Manalagi apple is a fruit with high antioxidant activity. Manalagi apple is a typical fruit of Batu City. Processed apple products are apple cider, vinegar, dodol, and chips. These products are sold in Batu city and produced the same home industry. The aim of this study was to determine the antioxidant activity comparison between Manalagi apple and four processed apple products based on IC50 values. This study used the ABTS method (2,2-azino bis (3-ethyl benzothiazoline-6-sulfonic acid) and analysis used spectrophotometric visible. IC50 value as apples and their processed products were analyzed using a one-way ANOVA. The study results indicated that IC50 value of Manalagi apple was insignificantly different from the processed apple product of dodol and chips. However, the IC50 value of manalagi apple was significantly different from apple cider and vinegar.